The expression of recombinant bacille calmette-guerin (rBCG) containing VPI gene of enterovirus 71 (EV71) - Wey, Goh Kai (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2008)
Enterovirus 71 (EV71) is a positive-sense single-stranded RNA, nonenveloped, icosahedrally symmetrical virus which was first detected in 1969 in United States. EV71 is associated with Hand-Foot-And-Mouth disease (HFMD) and some of EV71 infections may proceed to neurological diseases and even death because of neurogenic pulmonary edema. To date, there is still no vaccine available against this disease. Mycobacterium bovis Bacille Calmette-Guerin (BCG) has been suggested to be an attractive vehicle for the delivery of foreign antigens to the immune system. The main purpose of this study is to express a recombinant BCG (rBCG) containing ubiquitin (UbGR)-VP1 fusion gene ofEV71. UbGR-VP1 protein was detected in the cell extract but not in the supernatant of the recombinant clone by Western blot analysis using rabbit polyclonal antibody specific to VP 1 protein. The immunogenicity of the rBCG is still unknown and can only be confirmed if further study is done.